Study on Temporal Effects of Urban Malaria Incidences - S. Ganguly, Krishnendra; Modak, Soumita; S. Ganguly, Krishna; K. Chattopadhyay, Asis (International Journal of Statistics in Medical Research, 2016)
In Africa and Asia Malaria is considered to be the most widespread vector-borne disease taking lives of many people and specially affecting children. Many parts of India are significantly affected by malaria over a long period of time. Kolkata is one of the Metropolitan cities in India where the seasonal effect of malaria is very common. In the present work attempts have been made to study temporal variation of urban malaria incidences using time series model on the basis of a large survey conducted by the Kolkata Municipal Corporation. It is found that the proposed time series model can be used successfully for prediction purpose.